2019
DOI: 10.1007/s40622-019-00208-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of celebrity factors, consumer attitude and involvement on shoppers’ purchase intention using hierarchical regression

Abstract: Upon scanning the existing literature on celebrity endorsement, it is observed that present studies have explored the influence of select celebrity endorsement factors or consumer factors on shoppers' purchase intention. However, these studies have not explored the cumulative effect of these antecedents on shoppers' intention to buy. Thus, the present study examines the impact of two celebrity endorsement factors-celebrity-product congruence and celebrity attractiveness, and three consumer factors-attitude tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 63 publications
2
32
0
2
Order By: Relevance
“…The results show the value ( = 0.663, p = <0.001). Then the fourth hypothesis is supported and in line with previous research which states that brand attitude is identified as an important construction affecting purchase intention that begins because MARCH 2021 Angga Febrian, Muhtad Fadly of the stimulus provided by celebrity endorsement (Arora et al, 2019).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The results show the value ( = 0.663, p = <0.001). Then the fourth hypothesis is supported and in line with previous research which states that brand attitude is identified as an important construction affecting purchase intention that begins because MARCH 2021 Angga Febrian, Muhtad Fadly of the stimulus provided by celebrity endorsement (Arora et al, 2019).…”
Section: Resultssupporting
confidence: 82%
“…fectiveness to achieve customer target (Till, 1998). The use of celebrities for product marketing has been discussed in many previous types of research especially to see the influence on brand attitude (Arora et al, 2019;Paul and Bhakar, 2018) as well as to see influence to purchase intention (Loureiro and Sarmento, 2019;Martínez-lópez et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Celebrities perceived to be knowledgeable, honest, and physically good looking are perceived to be trustworthy and thus, encourage positive attitudinal and behavioural reactions of the consumers (Ohanian, 1991). As per Arora et al (2019), celebrity attractiveness has a favourable impact on consumers' purchase intentions whereas celebrity congruence and consumer involvement have insignificant influence on purchase intention. The congeniality factor that transforms into a more positive attitude toward the brand augments the shopper's connection with the brand and signifies a direct association to purchase intention (Praxmarer, 2009).…”
Section: Celebrity Attractiveness and Consumer Involvementmentioning
confidence: 94%
“…A classic and useful definition about celebrity for this study is "any individual who enjoys public recognition and who uses this recognition on behalf of a consumer good by appearing with it in an advertisement" [8]. Recently, Arora et al [18] in their research strongly supported the influence of celebrity on consumer's buying behavior. Celebrities that appear on green advertising generate an attractive message and thus a large impact on the brand [19] and influences consumer's attitude toward advertisements of green products [12,20,21].…”
Section: Celebrity Characteristicsmentioning
confidence: 99%